2020
DOI: 10.1101/2020.04.20.20072355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hospital-treated infectious diseases and the risk of dementia: multicohort study with replication in the UK Biobank

Abstract: Background: Infectious diseases have been hypothesised to increase the risk of dementia. However, the evidence is sparse, captures only a limited range of infectious diseases, and relies on short follow-up periods. We assessed a wide range of severe (hospital-treated) bacterial and viral infections and their subtypes as risk factors for dementia in three large cohorts followed up for almost two decades and replicated the main findings in the UK Biobank. Methods: For primary analysis, we pooled individual-level… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a seminal study published in 2009, recent inflammatory events were associated with increased levels of peripheral immune markers and a twofold increase in the rate of cognitive decline over a 6-month period 58 . With regard to longer-term outcomes, a recent study showed that a history of infections requiring hospital treatment was associated with future development of dementia, even when analyses were limited to individuals in whom dementia was diagnosed more than 10 years after the infection 59 . Of note, such infections were more strongly associated with vascular dementia than with AD dementia, suggesting that infection-related mechanisms involve both inflammatory and vascular pathways 59 .…”
Section: State Of the Fieldmentioning
confidence: 99%
“…In a seminal study published in 2009, recent inflammatory events were associated with increased levels of peripheral immune markers and a twofold increase in the rate of cognitive decline over a 6-month period 58 . With regard to longer-term outcomes, a recent study showed that a history of infections requiring hospital treatment was associated with future development of dementia, even when analyses were limited to individuals in whom dementia was diagnosed more than 10 years after the infection 59 . Of note, such infections were more strongly associated with vascular dementia than with AD dementia, suggesting that infection-related mechanisms involve both inflammatory and vascular pathways 59 .…”
Section: State Of the Fieldmentioning
confidence: 99%
“…The key findings are that individuals hospitalized for CNS infections (bacterial or viral), as well as bacterial infections confined to the periphery, e.g. urinary tract, skin, and respiratory, had significantly greater risk of developing dementia over a prolonged observational period than did those with no hospitalizations for infection (7,54,55). Moreover, CNS infections inflicted the greatest risk of dementia with an adjusted hazard ratio (aHR) of 3.01 [95% CI 2.07 -4.37], even though non-CNS infections also conferred an excess risk (aHR 1.47 [95% CI 1.36 -1.59] (7).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a declining incidence of neurological diseases caused by meningitis in developed countries (4, 5), meningitis remains the 4 th leading cause of neurological disability-adjusted life-years globally (6). Additionally, recent data from a Finnish multicohort observational study found that individuals experiencing a CNS infection were 3-times more likely than uninfected individuals to develop dementia over a median follow-up period of 15.4 years (7). Host inflammatory responses are key drivers of post-infectious neurological dysfunction (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these patients are afflicted with SAE. Studies involving large patient cohorts provided robust evidence for the increased risk of developing dementia after severe systemic inflammation 1 . Post-infectious long-term cognitive dysfunction results not only in major disability of afflicted patients but causes also an immense burden on primary caregivers and the health care system 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that severe systemic infections may lead to long-term cognitive dysfunction with the risk of developing dementia. 1,2 Sepsis as the most severe manifestation of systemic infection is defined as a life-threatening organ dysfunction caused by an overwhelming and dysregulated host response to inflammation. 3 Sepsis is a world-wide health problem with increasing incidence and high mortality.…”
Section: Introductionmentioning
confidence: 99%